Infra-Low Frequency Neurofeedback rapidly ameliorates schizophrenia symptoms: A case report of the first session - Nestoros, Joannis N.; Vallianatou, Nionia G. (Frontiers in Human Neuroscience, 2022)
A thirty-eight years old army officer started therapy in 2020 with a four-year history of auditory hallucinations and delusions of reference, persecution and grandeur, symptoms which were resistant to traditional antipsychotic medications. He follows an integrative psychotherapy program which aims to reduce his anxiety, continues his antipsychotic medications, and has Infra-Low Frequency Regime Neurofeedback. After his initial assessment he had a forty minutes session of Infra-Low Frequency Regime Neurofeedback before any other kind of intervention. Before and immediately after the session he completed the SCL-90 scale and the Visual Analogue scale covering 20 aspects of his psychological and physical state as well as his schizophrenic symptoms. This first Neurofeedback session had dramatic effects on his psychotic symptoms, levels of anxiety and psychosomatic condition, before his first psychotherapy session and/or any changes in his antipsychotic medication. The above results have great importance due to the severity and chronicity of schizophrenia.